Effects of diet quantity on growth performance of juvenile sea cucumbers Holothuria scabra - Al-Harbi Mamdouh (Oceanological and Hydrobiological Studies)
Sea cucumbers are in high demand in the world market due to their nutritional and medicinal values. In this study, the growth performance of juvenile sea cucumbers Holothuria scabra fed with different proportions of two feeds was analyzed. Commercially available sea cucumber feed (feed-A) and formulated feed (feed-B) were used for the experiments. Animals fed with 2% feed-A showed a negative growth rate. Maximum growth was observed in animals fed with 8% feed-A and feed-B. While feed-A treated groups showed significant variation (P < 0.05) in growth performance between different percentages of diets, feed-B treated animals showed no such variation. Feed-B treated animals showed higher growth rates compared to feed-A treated sea cucumbers. Water quality parameters and anoxic conditions of the soil in culture tanks did not change due to the higher percentage of feeds. In conclusion, this study showed that diet percentage is an important factor for the optimum growth of sea cucumbers.